2019
DOI: 10.3389/fpsyt.2019.00822
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Sleep Quality on the Relationship Between Problematic Mobile Phone Use and Depressive Symptoms in College Students

Abstract: Background and Aim: Problematic mobile phone use (PMPU) and depression are great public health concerns among adolescents. The aim of this study was to determine the association between PMPU and symptoms of depression, as well as the mediating role of sleep quality. Methods: A total of 4,624 college students participated in this study. The Self-rating Questionnaire for Adolescent Problematic Mobile Phone Use (SQAPMPU), Pittsburgh Sleep Quality Index (PSQI), and Patient Health Questionnaire-9 (PHQ-9) were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
2
27
0
4
Order By: Relevance
“…The 28 excluded participants were ineligible due to age, or noncompletion of the SAS-SV or items from the PSQI score. Of those included, 38 of the SAS-SV score, and 85 of the adapted [18][19][20][21][22][23][24][25][26][27][28][29][30], where 92.1% (n = 961) were aged under 26, and 73.2% (n = 763) of the participants were female ( Table 1). In terms of smartphone usage, 23.7% (n = 247) used their phones for 3 h per day, while 18.5% (n = 193) used their phones for more than 5 h daily.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 28 excluded participants were ineligible due to age, or noncompletion of the SAS-SV or items from the PSQI score. Of those included, 38 of the SAS-SV score, and 85 of the adapted [18][19][20][21][22][23][24][25][26][27][28][29][30], where 92.1% (n = 961) were aged under 26, and 73.2% (n = 763) of the participants were female ( Table 1). In terms of smartphone usage, 23.7% (n = 247) used their phones for 3 h per day, while 18.5% (n = 193) used their phones for more than 5 h daily.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
“…In particular, smartphone use close to sleep initiation has been shown to delay circadian rhythm and found associated with total sleep time, where longer usage was associated with poor sleep ( 25 ). Furthermore, poor sleep outcomes may mediate the relationships between smartphone addiction and psychopathological symptoms ( 26 ). However, despite consistent advice from health bodies concerning the negative impacts of smartphone use on sleep, the majority of adults in the UK use their phones during the night and close to bed time ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in individuals with PMPU, constant exposure to blue light can inhibit the secretion of melatonin, and cause sleep and circadian rhythm disorders [40,41], which might be an important factor in the generation of psychopathological symptoms such as depression [42]. Previous studies have explored the mediating role of sleep quality between PMPU and depressive symptoms using crosssectional study designs [43,44]. However, there have also been studies with conflicting results, in which depressive symptoms played a mediating role between PMPU and sleep quality [45].…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Studies of the relationship between PMPU and mental health, especially those on depression, have received more attention in recent years ( Demirci et al. , 2015 ; Zou et al. , 2019 ; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%